The deployment of ICT facilities in teaching and learning in higher education: a mixed method study of its impacts on lecturers and students at the university of Ilorin, Nigeria - Shittu, Nafisat Afolake Adedokun (Institute of Education, International Islamic University Malaysia, 2012)
This study employed a triangulation convergence mixed method design consisting of both qualitative and quantitative procedures to examine the impact of ICT deployment in teaching and learning at the University of Ilorin, Nigeria. It studied the impacts of ICT in teaching and learning, the predictors of ICT impact and how ICT is utilized and integrated in teaching and learning at the university. The survey data were drawn from 593 respondents (students and lecturers) and was analyzed using factor analysis and linear regression, For the interviews, one-on-one and focus group interviews were conducted among seven students and eight lecturers to seek their varying opinion on ICT impact on teaching and learning in the university. Lecture-room observations were conducted across three classes from three faculties to see how ICT is utilized and integrated in the university. The findings gathered through these various means were triangulated, compared and contrasted to validate the study. Five underlying impact of ICT were generated through factor analysis. They are: improved students' learning, improved learning output, task enabler, collaborative assessment and psychosocial aid. Predictors of ICT impact were found to be perceived impact, integration, motivation and challenges. The qualitative interview provided answers to research questions 1, 2 and 3. The interview findings generated four themes namely: positive effects, integration, incentives and challenges. It also found that ICT integration across faculties differ and science-based courses integrate ICT better than other courses. The observation findings were situated under the four themes generated from the interview findings and confirmed that the Faculty of Sciences and the Faculty of Communication and Information Sciences integrate ICT better than the Faculty of Law. The findings of this study produced a model that serves as a conceptual framework for researchers on impact assessment. The model is made up of the predictors of ICT impact generated from this study and named ICT Impact Assessment Model. The components of this model as generated from this study are: positive effects, challenges, incentives and integration.